The Communist Manifesto and the meaning of revolutionary action - Sánchez, Félix Ruiz (Pontifícia Universidade Católica de São Paulo, 2004)
With the publication of the Manifesto, Marx and Engels created the founding discourse of modern revolutionary action. Putting the struggle for human emancipation in the centre of the concerns of theorists and activists of the preletariat movement, Marx and Engels provided socialist thought with an utopian and strategic horizon that remains valid until today.